Pathologic Response Rate After Concomitant Neo-Adjuvant Radiotherapy and Chemotherapy for Adenocarcinoma of the Uterine Cervix: A Retrospective Multicentric Study. Issue 5 (1st June 2010) - Poujade, Olivier; Morice, Philippe; Rouzier, Roman; Madelenat, Patrick; Lecuru, Fabrice; Muray, Jean-Michel; Mathevet, Patrice; Alran, Séverine; Salmon, Remy J.; Reyal, Fabien
Abstract : Introduction: Exclusive chemoradiotherapy (including brachytherapy) is the current standard of care for locoregionally advanced cervical cancer. The aim of the present study was to evaluate the responsiveness and to identify factors predicting the response to concomitant chemoradiotherapy before surgery in cervical adenocarcinoma. Methods: A multicentric retrospective study was done in 9 French centers. A total of 54women with cervical adenocarcinoma stage IB2 to IIIB who had undergone concurrent chemoradiation therapy followed by surgical treatment were included. The patients were stratified by histopathologic response after concomitant chemoradiotherapy (lesions smaller than 1 cm or larger). Results: The median (SD) age at diagnosis was 44.2 (12.4) years (range, 19.3-77 years). The median (SD) follow-up duration was 30.9 (36.5) months (range, 4.1-17 years). After clinical evaluation, the mean (SD) tumor size was 5 (1.2) cm (range, 2-7 cm). The patients achieved a clinical complete response after concurrent chemoradiation in 18 cases (33.5%). Pathologic residual tumor was noted in 36 cases (67%); tumors smaller than 1 cm were found in 18 cases (33.5%), and lesions greater than 1 cm were observed in 18 cases (33.5%). Factors being associated with a significant decreased sensitivity to neoadjuvant chemoradiotherapy were the following: menopause ( P = 0.012), parametrial invasion ( P < 0.001), lymphvascular space invasion ( P = 0.003), and mucinous subtype ( P = 0.001). Conclusions: Identification of predictive markers associated with incomplete response to neoadjuvant chemoradiotherapy in cervical adenocarcinoma may prove clinically useful and implement an individualized treatment plan.